ALBANIA'S ECONOMIC POLICIES IN THE CONTEXT OF EUROPEAN SOCIAL MODEL - Hoti, Ulpian (European Scientific Journal, ESJ, 2015)
This paper examines the key aspects of the main social insurance programs development in Europe, and in Albania, during different periods of time, in order to face the elements of this model, as well as the respective development. Employment and a welfare regime are both the key elements of the social model. The first element refers to the way how industrial relations are regulated, the skills development and wage settlements. The second element refers to the way how social protection is organized and social services are provided by the state, market and family in the production and distribution of welfare. Employment and welfare regimes are related, but not necessarily coherent in a wide period and intensive institutional change. The paper notes that dimension of the state welfare in the economic system is a sensitive topic in European integration. This is due to the emphasis given to the purpose of the competition, closely linked to the EU, as well as the strong relation between European social model and integration in the European Union, whose candidate status also Albania holds.